Cervical plexus block - safe anesthesia for the patients with massive mediastinal lymphadenopathy - Ivošević Tjaša; Ranković-Ničić Ljiljana; Mirić Ljubiša; Jotić Ana; Bukurov Bojana (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction. General anesthesia is frequently employed in neck surgery procedures. However, in patients at high risk for general anesthesia, regional anesthesia options, such as the superficial cervical plexus block, warrant careful consideration. Patients with mediastinal lymph node enlargement face an elevated risk of airway obstruction and hemodynamic mediastinal instability during anesthesia induction. In selected neck surgeries, including thyroglossal cyst excision, thyroglossal fistula repair, bronchial cyst removal, thyroidectomy, and lymph node excision, the superficial cervical plexus block presents a viable and secure alternative to general anesthesia. Case report. This report details the case of a patient with mediastinal lymphadenopathy and multiple brain metastases who underwent cervical lymph node excision. Given the patient’s severe comorbidities, pronounced risk of complete distal airway obstruction, hemodynamic instability, and the potential for compression effects from mediastinal mass, a superficial cervical block was administered. This block facilitated effective perioperative analgesia without inducing respiratory or cardiovascular instability. Conclusion. The superficial cervical plexus block emerges as a prudent alternative to general anesthesia in high-risk patients requiring cervical lymph node excision procedures. Its utilization should be considered in such cases to enhance patient safety and perioperative management.